Роль позвоночных в биоиндикации загрязнения среды хлорорганическими пестицидами - Шебунина, Н.A.; Маслова, О.В. (Вестник зоологии, 1999)
В работе представлены данные о накоплении хлорорганических пестицидов в абиотической среде и биоте. Рассчитаны коэффициенты накопления и коэффициенты межуровневого накопления пестицидов, которые можно использовать в биоиндикации. Предложены оригинальные решения эффективного поиска организмов-индикаторов. Приведены данные по изменению белкового обмена у вида-индикатора — лесной мыши (Apodemus sylvaticus Linneus, 1758), у которой существенно снижено содержание коллагена в костях позвоночника. При выборе вида-индикатора рекомендовано учитывать его биологические особенности. The work concerns data on the accumulation of organochlorinc pesticides in the abiotic environment and the biota. Calculations have been made of the accumulation coefficient and of the inter-level accumulation coefficient, which may be used for bioindication pur-poses. Proposals have been made for an original solution of the efficient search of indicator organisms. Data are presented on changes of physiological and biochemical indices of the organism of rodents, particularly of the forest-mouse (Apodemus sylvaticus Linneus, 1758), selected as the species-indicator which shows a significant decrease of the content of collagen in spine bones. When choosing the species-indicator, it is recomended to take into consideration its biological peculiarities.